Involvement in Maternal Care by Migrants and Ethnic Minorities: A Narrative Review - de Freitas, C (2020)
Background: Guidelines for improving the quality of maternal health services emphasise women's involvement in care. However, evidence about migrant and ethnic minorities' preferences for participation in maternal care remains unsystematised. Understanding these populations' experiences with and preferred forms of involvement in care provision is crucial for imbuing policies and guidelines with sensitivity to diversity and for implementing people-centred care. This paper presents a narrative synthesis of empirical studies of involvement in maternal health care by migrants and ethnic minorities based on four key dimensions: information, communication, expression of preferences and decision-making. Methods: Studies indexed in PubMed and Scopus published until December 2019 were searched. Original quantitative, qualitative and mixed methods studies written in English and reporting on migrant and ethnic minority involvement in maternal care were included. Backward reference tracking was carried out. Three researchers conducted full-text review of selected publications. Results: In total, 22 studies met the inclusion criteria. The majority of studies were comparative and addressed only one or two dimensions of involvement, with an emphasis on the information and communication dimensions. Compared to natives, migrants and ethnic minorities were more likely to (1) lack access to adequate information as a result of health care staff's limited time, knowledge and misconceptions about women's needs and preferences; (2) report suboptimal communication with care staff caused by language barriers and inadequate interpreting services; (3) be offered fewer opportunities to express preferences and to have preferences be taken less into account; and (4) be less involved in decisions about their care due to difficulties in understanding information, socio-cultural beliefs and previous experiences with care provision less attuned with playing an active role in decision-making and care staff detracting attitudes. Conclusion: Constraints to adequate and inclusive involvement in maternal care can hinder access to quality care and result in severe negative health outcomes for migrant and ethnic minority women. More research is needed into how to tailor the dimensions of involvement to migrant and ethnic minorities' needs and preferences, followed by provision of the resources necessary for effective implementation (e.g. sufficient time for consultations, optimal interpreter systems, health care staff training).